STUDY OF PREVALENCE AND ANTIFUNGAL SUSCEPTIBILITY OF CANDIDA. - AMAR C.S; ASHISH J; VINAY HAJARE; SREEKANTHA; YOGESH B; VINODCHANDRAN (International Journal of Pharma and Bio Sciences, 2013)
The yeast like fungus candida is the most common fungal pathogen causing disease in the human beings. As the disease is usually chronic and treatment failure cases were commonly noted , so the study was conducted to know the prevalence and antifungal susceptibility pattern of various candida species isolated from clinical samples. A total of 1702 subjects were selected, among which 60.2%were male and 39.8% were female. The identification of various candida species was done by saline wet mount, 10% KOH mount, Gram stain, germ tube test, culture on SDA, Chromagar, cornmeal agar, sugar fermentation tests and sugar assimilation tests. Antifungal susceptibility test was done by disc diffusion method.103 candida species were isolated from 1702 samples. Candida albicans is the most common species isolated from clinical specimen and the infection is almost same in both the sexes and predisposing factors like diabetes mellitus, prolonged contact it water were noted. They were advised correct treatment for diabetes mellitus, to limit the contact with water and maintenance of good personal hygiene.